2015
DOI: 10.4244/eijv11i6a137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of suture-based vascular closure devices in transfemoral transcatheter aortic valve implantation

Abstract: Patients undergoing transfemoral TAVI had significantly lower rates of vascular complications and percutaneous closure device failures when the Prostar was used compared with two ProGlide devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 18 publications
8
49
1
Order By: Relevance
“…The Prostar XL suture‐mediated closure systems are also widely used to achieve haemostasis after TF‐TAVI. Some studies compared the effectiveness of the Prostar and ProGlide, but the results were controversial . These studies underline the importance of the use of an optimal deployment technique.…”
Section: Discussionsupporting
confidence: 44%
“…The Prostar XL suture‐mediated closure systems are also widely used to achieve haemostasis after TF‐TAVI. Some studies compared the effectiveness of the Prostar and ProGlide, but the results were controversial . These studies underline the importance of the use of an optimal deployment technique.…”
Section: Discussionsupporting
confidence: 44%
“…The reported preference of Prostar XL over Proglide use in Polish centres depends on local practice. Current conflicting reports on the safety of closure device use in TAVI suggest the need for further research in this field [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…The current study found no significant clinical differences between percutaneous preclose techniques using a single or double Perclose ProGlide devices in patients undergoing TF‐TAVI. Several previous reports revealed the feasibility of percutaneous femoral artery closure devices for the management of large‐caliber sheaths during TF‐TAVI . The success rates of femoral artery hemostasis using double Perclose ProGlide devices in the literature range from 80.5% to 93.9% .…”
Section: Discussionmentioning
confidence: 99%
“…The Prostar XL and Perclose ProGlide (Abbott Vascular, Santa Clara, California) suture‐mediated closure systems are widely used for this purpose. The preclose technique is required for the adoption of this less invasive percutaneous approach during TF‐TAVI, whereas the debate is ongoing as to which devices are superior or how many such devices are needed to achieve hemostasis . The technical aspects of the reported ProGlide method involve double suturing using two ProGlide devices before insertion of a large‐caliber sheath , and comparative data in the literature comparing single and double ProGlide techniques after percutaneous TF‐TAVI are limited.…”
Section: Introductionmentioning
confidence: 99%